Increasing Educator Loyalty in Achieving Quality of Learning - Sunardi Sunardi; Nurwanto Nurwanto (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2024)
Madrasa headmasters are responsible for developing the loyalty of their educators in order to improve student learning quality. Educators need to demonstrate their abilities to meet their school's interests and improve the quality of learning and student achievement. This research focuses on how the headmaster of the madrasa improves the learning quality at MA-Al Urwatul Wutsqo Jombang. This research is descriptive qualitative research. The data collection techniques used were interviews, observation and documentation. The finding shows that to improve learning quality in the madrasah, the headmaster builds collaboration with the madrasa foundation or owner through which human resources, especially the teaching staff, have been managed and developed. In addition, the headmaster is able to recruit the teaching staff based on the needs, professionalism, evaluation, and coaching system